Peculiarities of the cavernous cerebral malformations diagnostic and treatment - Tsimeyko, O. A.; Goncharov, A. I.; Orlov, M. Yu.; Skorokhoda, I. I.; Chernenko, O. G. (Ukrainian Neurosurgical Journal, 2006)
On the basis of analysis of 49 cerebral malformations observations are analyzed and the peculiarities of their diagnostic and treatment were distinguished. Observation data and results of the patients surgical treatment with microsurgical technique application substantiate the necessity of more active operative interventions usage at this complex vascular cerebral pathology treatment.